Musharakah Mutanaqisah home financing products: an implementation analysis, product advantages and issues at Citibank (Malaysia) Berhad - Borhan, J.T.; Shuib, M.S.; Abu Bakar, A. (2011)
Banking institutions in Malaysia consists of two categories, the full-fledge Islamic banks and interest-free banking scheme. Banks offering Islamic products that are purely local and some from outside, such as Citibank (Malaysia). This research discuses the concept of Musharakah Mutanaqisah in Islamic transaction and its application in the home financing product at Citibank Malaysia Berhad. The research focuses on how does this syariah concept apply on Islamic home financing product, their advantages, issues and challenges that was faced by this institution. In order to achieve the objectives of the research, the researcher used the library and fields work methods to collect the data. The data collected was analyzed using the methods of inductive and deductive and comparative. This research shows that home financing through Musharakah Mutanaqisah is a new product, offered from 2005. Musharakah Mutanaqisah is a hybrid contract and created by some elements like ijarah, al-bay‘, Musharakah. Research finding also shows that the impact of the use of Musharakah Mutanaqisah instrument is better than previous contract like BBA. This indirectly explain to us how conventional banks like Citibank offers Islamic banking products through Windows Islamic Banking schemes.